Promoting of Creative Tourism Based on Community Participation in Surin Province - Kuthaweekul, Chokdee; Na Thalang, Chawalee (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2025)
This research article aimed to 1) study the components of tourism (10A's) and the component of creative tourism destination management, 2) study the community participation process in promoting creative tourism, and 3) present guidelines for promoting creative tourism based on community participation in Surin Province. This qualitative research used in-depth interviews with 22 key informants from the government sector, private sector/entrepreneur, community sector, and academic sector. This article analyzes the data by examining the triangular data and SWOT Analysis, TOWS Matrix. The results found that 1) the tourism components (10A’s) in Surin Province are outstanding in six elements: attraction, accommodation, amenity, activity, atmosphere, and amiability, and four elements of tourism improvement: accessibility, ancillary, availability, and authority. As a component of creative tourism destination management, Surin Province has many communities with the potential to support creative tourism activities. Communities are willing to cooperate in organizing various tourism activities, which can create impressive tourist experiences. 2) Community participation involves holding meetings to propose tourism activities, dividing responsibilities based on the expertise and resources available in each family, determining the proportion of profit sharing, recording tourist statistics, recording income and expenses, and holding meetings to report problems after organizing activities. The community receives assistance and advice from relevant agencies. 3) Guidelines for promoting creative tourism based on community participation: Propose guidelines for SO strategies, WO strategies, ST strategies, WT strategies, and 14 strategies. The SMART Model is a new way of thinking about things. It includes S (Synergy), which means that the public, private, and community sectors should work together; M (Marketing), which means that marketing and communication should be integrated; A (Activity), which means tourism activities; R (Resource), which means tourism staff; and T (Training), which means training for tourism staff.